Metal-Supported Perovskite as an Efficient Bifunctional Electrocatalyst for Oxygen Reduction and Evolution: Substrate Effect. Issue 3 (2nd March 2021) - Soltani, Mohammad; Amin, Hatem M.A.; Cebe, Atilla; Ayata, Sevda; Baltruschat, Helmut
Abstract : Due to increased energy demand and environmental concerns, sustainable energy systems such as electrolyzers and Li-air batteries have attracted significant interest. However, it is imperative to develop an efficient inexpensive catalyst for the underlying reactions, namely oxygen reduction (ORR) and evolution (OER) reactions, to overcome their sluggish kinetics. In our previous work, a combination of silver and Co3 O4 particles showed high bifunctional activity. Herein, we extend the study to investigate how the electrocatalytic activity is dependent on the oxide composition and the type of the underlaying substrate. A significant enhancement in OER performance is realized at perovskite-supported silver or gold electrodes with activity decreasing in the order Ag≥Au>GC. This is attributed mainly to a synergistic interaction between the oxide and metal support and the enhanced conductivity. The ORR activity observed at oxides loaded on Ag and Au bulk electrode is similar, however they exhibit about 450 mV lower overpotential than on GC. The improved activity at oxides/metal substrate renders this approach promising for O2 -electrodes design.